KONSEP DEMOKRASI DALAM KEHIDUPAN EKONOMI DAN POLITIK MENURUT PERSPEKTIF ARTHASASTRA - Untung Suhardi (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2013)
Abstract Arthasastra book first examines community by explaining the purpose trayi, anvikshiki, Varta, and danda within the framework of human existence. Then went on to explain warnasrama dharma as the foundation of social order and the general obligations that apply to everyone. As a statesman, Kautilya pay great attention to work and power. Arthasastra reflected elements of democracy, as described in the conception of democracy among other kingdoms or states recognize diversity; folk in the free association or organization; cooperation are independent and harmonious; seek justice; contained the separation and division of powers; powers acquired under the law; election of state officials based on moral qualities and skills; government policy implemented by law; carried out in a planned leadership succession; no freedom of individuals to develop their talents and interests; ensure the protection of the rights and welfare; magnitude of taxes and trading profits stipulated by the agreement, and dispute resolution institutionalized by prioritizing peace. Key Word: Democracy, Arthasastra, politics and the state.